(3efgL,CSdhH,hSjdIs - (3GdCMO OQjfI(B, (3YKeGfs; (3NOGe(B, (3YKeGf jhSas ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2005)
(3GdCgOGa GdJQHhjI;GdefgL;GSJQGJjLjI GdJYdje;WQGFb GdJOQjS;GdCSGdjH GdeJHYI aj GdJOQjS;GdhSGFd GdJYdjejI;GdJbhje;GdJNWjWj ddOQSs
Keywords: (3GSJQGJjLjI GdJYdjes; (3GdCgOGa GdJQHhjIs; (3GdJbhjes; (3GdefgLs; (3GdhSGFd GdJYdjejIs; (3WQGFb GdJOQjSs